Literacy as a resource to build resilency - Rojas, Laura Katherine (Colombian Applied Linguistics Journal, 2014)
Searching for ways in which readers can transform their reality in a critical way, Chapetón (2007)worked within a group of displaced adults in a reading club where they were able to share perspectives, backgrounds, and emotions regarding their own problematic issues by using a dialogic basis. In our field, it is important that more pedagogues observe these activities as a manner of exploring students’ thoughts. Chapetón was able to accomplish this by examining an interdisciplinary background as psychology to more deeply understand the reader’s world reality.